Peluang Sampah Bleaching Earth (Bentonite) dan Bakteri Pelarut Silika Sebagai Sumber Silika untuk Induksi Produksi Metabolit Sekunder Pada Tanaman - Cico Jhon Karunia Simamora; Ellia Septiarahma Rumambi; Tika Widya Pratiwi; Ajeng Maula Ningrum; Taris Zharfan Mias Embau (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: CPO refining which produces solid waste namely spent bleaching earth (SBE) in large quantities can pollute the environment. SBE from bentonite ores contains large amounts of silica, so it can be an alternative source of silica minerals. Silica plays an important role in increasing plant resistance and bioactive plant compound products. Methods: The application of Si in plants can increase secondary metabolites such as phenolic and anti-fungal compounds in response to disease pathogens. However, the low solubility of silica makes silica not sufficiently available for plants. Using microorganisms as silica solubilizing bacteria helps increasing solubility of silica in the soil. Bacteria dissolve silica by removing organic acids and producing indole acetic acid (AAI), which stimulates root hairs. Results: This review presents the results of a study on the utilization of silica-rich SBE waste as a source of available silica for plants with solubilizing method using bacteria to increase plant growth and resistance, as well as increase plant secondary metabolite compounds. Conclusions: The application of silica solubilizing bacteria has been known to play an important role in providing silica for plants, through enzymatic mechanisms, namely the production of organic acids and extracellular polysaccharides.